2015
DOI: 10.1371/journal.pone.0137137
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Coronary Heart Disease in Patients with Primary Fibromyalgia and Those with Concomitant Comorbidity—A Taiwanese Population-Based Cohort Study

Abstract: ObjectivesFibromyalgia has seldom been associated with coronary heart disease (CHD). The aim of this study was to evaluate the risk of CHD in patients with fibromyalgia.MethodsWe used a dataset of one million participants, systemically scrambled from the Taiwanese national insurance beneficiaries, to identify 61,612 patients with incident fibromyalgia (ICD-9-CM 729.0–729.1) and 184,834 reference subjects matched by sex, age and index date of diagnosis in a 1:3 ratio from 2000 to 2005, with a mean 8.86 ± 2.68 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…Studies have revealed that apart from traditional inflammation-related cardiovascular risk factors, such as diabetes (4,5,9,10), hyperlipidemia (4,9,10), hypertension (4,5,9,10), depression (1-5,9,10), anxiety (1)(2)(3)(4)(5)(8)(9)(10), and sleep disorders (1)(2)(3)(4)(5)(6)8,10), diseases characterized by inflammatory processes (e.g., RA (14,15) and SLE (15,16)), and infectious courses (such as HCV (11)(12)(13) and HIV (11)(12)(13)) can also enhance the risk of FM. In addition to these well-known inflammatory sources, other less-notified inflammatory diseases (e.g., IBD) should be considered as possible causes of FM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have revealed that apart from traditional inflammation-related cardiovascular risk factors, such as diabetes (4,5,9,10), hyperlipidemia (4,9,10), hypertension (4,5,9,10), depression (1-5,9,10), anxiety (1)(2)(3)(4)(5)(8)(9)(10), and sleep disorders (1)(2)(3)(4)(5)(6)8,10), diseases characterized by inflammatory processes (e.g., RA (14,15) and SLE (15,16)), and infectious courses (such as HCV (11)(12)(13) and HIV (11)(12)(13)) can also enhance the risk of FM. In addition to these well-known inflammatory sources, other less-notified inflammatory diseases (e.g., IBD) should be considered as possible causes of FM.…”
Section: Discussionmentioning
confidence: 99%
“…Because FM-associated comorbidities were more commonly seen among the older population (2,4,10,13), the most important risk factor for FM was age, especially old age (2,4,10,13). The age-related effect on FM development was also reflected in the FM incidences in both the IBD and non-IBD groups (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations